Constructing a Stable Interface Layer by Tailoring Solvation Chemistry in Carbonate Electrolytes for High‐Performance Lithium‐Metal Batteries. Issue 8 (14th January 2022) - Piao, Zhihong; Xiao, Peitao; Luo, Ripeng; Ma, Jiabin; Gao, Runhua; Li, Chuang; Tan, Junyang; Yu, Kuang; Zhou, Guangmin; Cheng, Hui‐Ming
Abstract: Lithium‐metal batteries (LMBs) are considered as promising next‐generation batteries due to their high energy density. However, commercial carbonate electrolytes cannot be used in LMBs due to their poor compatibility with the lithium‐metal anode and detrimental hydrogen fluoride (HF) generation by lithium hexafluorophosphate decomposition. By introducing lithium nitrate additive and a small amount of tetramethylurea as a multifunctional cosolvent to a commercial carbonate electrolyte, NO3 −, which is usually insoluble, can be introduced into the solvation structure of Li + to form a conductive and stable solid electrolyte interface. At the same time, HF generation is suppressed by manipulating the solvation structure and a scavenging effect. As a result, the Coulombic efficiency (CE) of Li||Cu half cells using the designed carbonate electrolyte can reach 98.19% at room temperature and 96.14% at low temperature (−15 °C), and Li||LiFePO4 cells deliver a high capacity retention of 94.9% with a high CE of 99.6% after 550 cycles. This work provides a simple and effective way to extend the use of commercial carbonate electrolytes for next‐generation battery systems. Abstract : Solvation chemistry in a commercial carbonate electrolyte is tailored by adding tetramethylurea cosolvent and an additive. As a result, a highly conductive and stable interface layer is constructed and lithium hexafluorophosphate decomposition is inhibited. This simple strategy can not only suppress Li‐dendrite growth and hydrogen fluoride production to prolong cycle life, but also enhances the temperature tolerance of lithium‐metal batteries.